Pendampingan Penentuan Harga Pokok Produksi Dan Harga Jual Produk Olahan Ikan Desa Karanganyar Kecamatan Kalianget - Astri Furqani; Arief Hidayatullah Khamainy; Dina Kurniawati; Rusnani Rusnani (BADAN PENERBIT STIEPARI PRESS, 2023)
In any business, whether it is a large-scale enterprise or a small and medium-sized business (MSME), it is essential to calculate the Cost of Production to determine the selling price accurately. The purpose of providing assistance in determining the cost of production and selling price to the entrepreneurs of processed fish products in Karang Anyar village is to increase their knowledge and improve the profits of the